PENGARUH FITUR LAYANAN, KEMUDAHAN DAN KEAMANAN TERHADAP KEPUASAN PENGGUNA E-WALLET APLIKASI DANA DI KABUPATEN KUTAI TIMUR - Ahmad Habibi; Saida Zainurrosalamia Za (CV. Armas Suan Sejahtera, 2025)
Indonesia is a country experiencing rapid technological development, including the adoption of financial technologies such as e-wallets. One of the popular e-wallet applications is Dana, which is used by many people in various regions, including Kutai Timur Regency. Kutai Timur, with its diverse population and increasing transaction needs, is an ideal location to study the factors influencing e-wallet user satisfaction. This study aims to examine the influence of service features, ease of use, and security on the satisfaction of Dana e-wallet users in Kutai Timur Regency. The independent variables in this study are service features, ease of use, and security, while the dependent variable is satisfaction. The population in this study consists of Dana e-wallet users who have used the application. This research employs purposive sampling and non-probability sampling techniques, with a sample size of 200 respondents. The type of data used is quantitative data, obtained directly through questionnaires. Data analysis in this study was conducted using Partial Least Square (PLS) with SmartPLS 4.0 to test validity, reliability, and the coefficient of determination (R2), as well as hypothesis testing. The results of this study indicate that service features have a positive and significant effect on satisfaction, while ease of use has a positive but not significant effect on satisfaction. Security has a positive and significant effect on the satisfaction of Dana e-wallet users in Kutai Timur Regency.